Hiatal Hernia Presenting with Recurrent Non‐ST Elevation Myocardial Infarction and Cardiac Tamponade - Arvind, Ashwini (ACG Case Rep J, 2019)
Hiatal hernia is a common pathology, particularly among the elderly or obese populations. Occasionally, markedly dilated hernias can impinge on surrounding structures, notably the heart or lung. In such cases, morbidity can be considerable. We present a case of an enlarging hiatal hernia that compressed the heart, leading to recurrent non-ST elevation myocardial infarction with cardiac tamponade. The patient was successfully managed with nasogastric decompression and surgical repair. We recommend that extrapericardial pathology be considered in tamponade patients with concurrent hiatal hernia and that surgery should be considered the definitive treatment modality.